Modern contraceptive use and associated factors among married women in Finote Selam town Northwest Ethiopia: a community based cross-sectional study - Geremew, Alehegn Bishaw (Womens Midlife Health, 2018)
BACKGROUND: A modern contraceptive method is a product or medical procedure that interferes with reproduction following sexual intercourse; however, contraceptive services remain out of reach for many women of reproductive age worldwide, resulting in millions of unwanted pregnancies and unsafe abortions each year. In addition to limiting the number of children, family planning is essential to promoting the well-being and autonomy of women, their families, and their communities. Factors influencing modern contraceptive utilization are multifaceted and challenging, therefore; this study aimed to assess modern contraceptive utilization and associated factors among mid to late reproductive age, married women in Finote Selam town, northwest Ethiopia. METHODS: A community based cross-sectional study was conducted from June 30 to July 15, 2017 among married women aged 30–49. A cluster sampling technique was used to select 1146 eligible participants from three randomly selected kebeles. A face-to-face interviewer administered a structured and pretested questionnaire. Binary logistic regression models, in bivariate and multivariable analyses, were fitted to identify factors associated with the outcome variable. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) was calculated to determine the presence, direction, and strength of associations. RESULTS: A total of 1134 women aged 30–49 participated in this study representing a response rate of 98.9%.The overall modern contraceptive utilization was 37% (95% CI 35.43–40.21). An injectable contraceptive was the most commonly used method, followed by an implant contraceptive method. Factors independently associated with modern contraceptive use were: educational status -secondary school (AOR = 1.5,95%CI 1.01–2.2) and college and above (AOR = 1.5,95%CI 1.02–2) compared to no education, number of previous pregnancy: nulligravid (AOR = 4.6,95%CI 3.2–5.5),1–2 previous pregnancies (AOR = 3.2,95%CI 2.03–5.44), 3–4 previous pregnancies(AOR = 2.3,95% CI1.4–3.7) compared to > 4 pregnancies and postnatal care utilization (AOR = 1.5,95% CI 1.1–2.1)compared to no postnatal service utilized. CONCLUSION: Our findings show that modern contraceptive utilization among women age 30–49 is low in Finote Selam town Northwest Ethiopia. Women’s educational status, low number of previous pregnancies and postnatal care service utilization during the last birth were independently associated with modern contraceptive method used. Providing modern contraceptives targeting grand multiparous women and women having no formal education is important. Improving postnatal care utilization is one potential strategy to enhance modern contraceptive utilization.